2021
DOI: 10.1002/slct.202100982
|View full text |Cite
|
Sign up to set email alerts
|

A Dicyanocarbazolylstilbene‐Derived Two‐Photon Fluorescence Probe for Lipid Raft with a Large Two‐Photon Action Cross Section

Abstract: Lipid raft is a microdomain which is rich in cholesterol and sphingolipid in the cytoplasmic membrane, and closely related to neurodegenerative diseases such as Alzheimer's disease and prion disease. Hence the study on the physiological mechanism of lipid raft is helpful to reveal its biological role and its correlations with diseases. Two-photon fluorescence probe for lipid raft is a sharp tool to achieve this goal. A dicyanocarbazolylstilbene-derived two-photon fluorescence probe for lipid raft (DLR) with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In previous exploration, we found that flexible substituents on the amino group not only significantly reduced the fluorescence quantum yield (Φ) and δ TPA [22][23][24][25][26] of a probe; but also increased the dependence on viscosity, which in turn, can highly weaken the dependence on temperature, thus giving rise to large measurement error. Therefore, we introduced a planar rigid 9-carbazolyl group at the amino terminus of DCS, which is a large aromatic ring and can further expand the molecular aromatic system with planar rigidity, thus significantly increasing the molecular Φ and δ TPA , and the dependence of the molecule on temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous exploration, we found that flexible substituents on the amino group not only significantly reduced the fluorescence quantum yield (Φ) and δ TPA [22][23][24][25][26] of a probe; but also increased the dependence on viscosity, which in turn, can highly weaken the dependence on temperature, thus giving rise to large measurement error. Therefore, we introduced a planar rigid 9-carbazolyl group at the amino terminus of DCS, which is a large aromatic ring and can further expand the molecular aromatic system with planar rigidity, thus significantly increasing the molecular Φ and δ TPA , and the dependence of the molecule on temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The reported two-photon fluorophore DCS (4-methyl-2,5dicyano-4'-amino stilbene) with a very large TPA cross section (δ TPA ) has been successfully applied in the designs and developments of various TPF probes. [21][22][23][24] DCS is a push-pull chromophore with donor-π-acceptor (D-π-A) architecture. Its rationality and optimization in structural design have been proved by the literature.…”
Section: Introductionmentioning
confidence: 99%